Traffic Signal Control That Consider The Trip Assignment - CENDRABUMI (NIM 15004048) dan MIRNA A. OCTORIA (NIM 15004082), MARISCA
One of the biggest problem in transportation sector is the high number of delay and queue that often happened in juction areas. That is why it is reasonable if driver will choose the route with longer green time although it will cause longer travel distances. In this case, driver will choose the minimum total cost which are consist of travel times and travel distances that will influence the Vehicle Operation Cost. This Final Assignment Research observes the influence of traffic signal control to the route choice that meant to fix the network performance which is judged by performance indicator such as distances, free flow speeds, saturation flows, and speed-flow relations with change the traffic signal skenario (green time and offset). There is one simple network and one real network that are gonna be modelled in this Final Assignment Research. The examination of simple network is to judge the influence of changing traffic signal control in determining route choice that will used for modelling the real network. The two modelling systems use Simulation and Assignment of Traffic to Urban Road Networks (SATURN) programme. The simple network has eight scenarios of traffic signal control. From those eight scenarios we choose one scenario that has minimum total cost transportation that falls to scenario 8 with total cost transportation Rp 3.468.963/hour and green time at first stage is 45 seconds while green time at second stage is 15 seconds. The real network has twenty four scenarios. From those, the scenario that product the minimum total cost transportation is scenario 22 with total cost transportation Rp 22.189.330/hour.